A case study for emergency management and urban resilience under seismic risks. Part III: an integrated digital platform for Digital Inspection and Monitoring Assistant (DIMA) - Ahmed Mebarki; Boumediène Oukaci; Khaled Meziani; Nabila Tahrat; Lakhdar Becheikh; Ali Brahimi; Amar Zekri; Nabila Houmer; Chahinez Alliche; Hadjer Boumeshad; Tarek Khiri; Younès Marouf; et al. (Emergency Management Science and Technology)
The current paper presents a digital platform developed to manage the damage evaluation campaign for buildings in the aftermath of earthquakes, or any event such as industrial explosions or fires, landslides, floods, or tsunamis. Scientific software, embedded in this platform, automatically derives the building's damage category, according to the damage observed on its constitutive components, during a quick visual inspection performed by trained and technical staff and engineers. The scientific methodology is adapted to the case of the evaluation form in use in the concerned countries. For illustrative purposes, this study focuses on the case of the Algerian evaluation form, although it can be adapted to other countries since the evaluation forms are very similar and based on empirical principles or calibrated according to past accidents. During the field inspection, the qualified staff complete the evaluation form on connected or non-connected digital devices i.e. PC, tablet, smartphone, and even paper sheets. As soon as the digital devices are connected, an immediate real-time or slightly delayed survey of the damage extent on GIS-based maps, with automatic reporting, becomes available to the authorities, owners, and stakeholders, depending on specific rights to access the platform. This is helpful in decision-making regarding the rescue, relief, and sheltering for the inhabitants who have no further access to the houses, offices, markets, factories, schools, health facilities, etc., if these places have to be evacuated until they are further investigated and repaired or demolished. This study reports real applications during recent earthquakes and stress tests.